2014
DOI: 10.1002/pon.3576
|View full text |Cite
|
Sign up to set email alerts
|

‘What is this active surveillance thing?’ Men's and partners' reactions to treatment decision making for prostate cancer when active surveillance is the recommended treatment option

Abstract: Objective: In the past decade localized prostate cancer (LPC) management has been shifting from three radical treatment options (radical prostatectomy, external beam radiotherapy, or brachytherapy) to also include active surveillance (AS). This study examines men with LPC and partners' experiences of choosing between AS and radical treatments, and their experiences of AS when selected.Methods: Qualitative descriptive research design. Interviewed participants were men, and partners of men, who had either chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
108
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 35 publications
4
108
1
Order By: Relevance
“…Study characteristics can be found in Table . Three studies were from the United States, two from Canada, and one each from the United Kingdom, Sweden, and Australia. Sample sizes of AS patients in cross‐sectional studies ranged from three to 431 (M = 169, SD = 229.6) and in qualitative studies ranged from four to 37 (M = 20.8, SD = 11.2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study characteristics can be found in Table . Three studies were from the United States, two from Canada, and one each from the United Kingdom, Sweden, and Australia. Sample sizes of AS patients in cross‐sectional studies ranged from three to 431 (M = 169, SD = 229.6) and in qualitative studies ranged from four to 37 (M = 20.8, SD = 11.2).…”
Section: Resultsmentioning
confidence: 99%
“…Information on PCa, signs of progression, future treatment options, and adjuvant treatments (such as diet and exercise) were reported as inadequately provided by the treating physicians and/or unavailable to patients. For instance, one man in Loeb et al's study explained he wanted to “know what progresses the cancer” as he currently felt “ignorant about the whole thing.” Several participants in the qualitative studies also reported that information regarding AS was too limited. Loeb et al noted men often needed more information regarding the follow‐up protocol, such as the ideal frequency and reason for performing tests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have reported that these men may be more likely to perceive worse care compared with those undergoing treatment, although on the basis of patient and physician characteristics, the findings are mixed. 45-47 …”
Section: Discussionmentioning
confidence: 99%